Health benefit of air quality improvement in Guangzhou, China: Results from a long time-series analysis (2006–2016). (May 2019) - Wu, Rongshan; Song, Xiaoming; Chen, Duohong; Zhong, Liuju; Huang, Xiaoliang; Bai, Yingchen; Hu, Wei; Ye, Siqi; Xu, Hongbing; Feng, Baihuan; Wang, Tong; Zhu, Yutong; et al.
Abstract: Numerous epidemiologic studies on adverse health effects of air pollution have been well documented; however, assessment on health benefits of air quality improvement from air pollution control measures has been limited in developing countries. We assessed the mortality benefits associated with air pollution improvement over 11 years in Guangzhou, China (2006–2016). A time series analysis with Generalized additive Poisson models was used to estimate mortality effects of ozone (O3 ) and nitrogen dioxide (NO2 ), adjusting for time trend, day of week, public holiday, temperature and relative humidity. We further estimated the changes in mortality burden of O3 and NO2, including attributable fraction (AF, in %) and attributable mortality (AM, in number of death) during study period. We lastly estimated mortality effects during the 2010 Asian Games (November 12 to December 18, 2010) compared to a baseline period consisting of 4-week before and 4-week after the game. During the study period, average annual concentrations of NO2 decreased from 42.3 μg/m 3 in 2006 to 33.8 μg/m 3 in 2016; while O3 levels remained stable over time. We observed significant increases in mortality of O3 and NO2, with approximately linear exposure-response relationships. In specific, each increase of 10 μg/m 3 in O3 and NO2 at 2 prior days was associated with increases of 0.60% (95% confidence interval (CI): 0.47, 0.74) and 1.89% (95%CI: 1.49, 2.29) in total mortality, respectively. We further estimated that AF on total mortality attributed to NO2 decreased from 1.38% (95%CI: 1.09, 1.68) in 2006–2010 to 0.43% (95%CI: 0.34, 0.52) in 2011–2016, corresponding to AM on total mortality of 2496 deaths (95%CI: 1964, 3033) to 1073 deaths (95%CI: 846, 1301). During the 2010 Asian Games, we observed decrease in total mortality of 9.3% (95%CI: −15.0, −3.2) in comparison with that observed in the baseline period. Similar mortality benefits in cardiovascular diseases were also observed. Our results showed reduced mortality burden from air pollution improvement in Guangzhou in recent years, which provide strong rationale for continuing to reduce air pollution through comprehensive and rigorous air quality management in the area. Highlights: Exposures to O3 and NO2 were significantly associated with mortality in Guangzhou, China. Reductions in mortality burden of NO2 following improved air quality during 2006–2016 Health benefits of improved air quality were observed during the 2010 Asian Games.